Pengaruh Penggunaan Metode Resitasi Terhadap Hasil Belajar Siswa Kelas Xl di SMA Negeri 1 Tondano - Cantika Mamuaya; Sjeddie Watung; Cherys Fonny Laloan (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
ABSTRACTThe aim of this research is to analyze and interpret the influence of the use of research methods on student learning outcomes in the Economics subject at State High School 1 Tondano. This research uses questionnaire data collection techniques and documentation. Questionnaire (questionnaire) is aimed at students to seek data about the use of research methods, and documentation that is aimed at obtaining information about economic learning outcomes, brief history of its founding, vision and mission, educational data and educational staff, student participant data, state of affairs sarana and infrastructure, organizational structure, SMA Negeri 1 Tondano location plan. The results of this research conclude that there is an influence of the research method on the economics learning outcomes of students in class XI at SMA Negeri 1 Tondano. This is proven from the results of hypothesis testing using the Chi Square formula, a calculated value of 23,647 is greater than the significant 5% table with a value of 9,488. So that in this research the alternative hypothesis (H_a) is accepted and (H_o) is rejected, with a very high level of influence. I As well as from the results of the calculation of the coefficient of determination, the use of the research method has a contribution or influence of 74.63% in influencing the results of learning Economics students of class XI SMA Negeri 1 Tondano.